PENGARUH QUICK RATIO TOTAL ASSET TURNOVER DAN RETURN on INVESTMENT TERHADAP HARGA SAHAM - Sari, Dian Indah (Universitas Muhammadiyah Palembang, 2020)
This study aims to determine the effect of Quick Ratio, Total Asset Turnover and Return on Investment on the share price of Pharmaceutical Industry companies listed on the Stock Exchange in the 2016-2019 period. This research is a quantitative descriptive study. This study took samples from pharmaceutical companies listed on the Indonesia Stock Exchange in the period 2016-2019. Data analysis used included multiple linear regression analysis. The conclusions of this study are as follows: The Quick Ratio (QR) variable has no significant effect and has a positive effect on stock prices. The Total Asset Turnover (TAT) variable has a significant effect and has a positive effect on stock prices. The Return on Investment (ROI) variable has a significant effect and has a positive effect on stock prices. Variable Quick Ratio (QR), Total Asset Turnover (TAT) and Return On Investment (ROI) simultaneously have a significant effect on stock prices